Healing effect of unguent from Dodonaea viscosa Jacq. “Chamisa” in Balb/C 53 mice - Alcedo, Carlos (2017)
Objectives: To determine the healing effect of ethanolic extract ointment on leaves of Dodonaea viscosa Jacq. "Chamisa" in Balb / c 53 mice. In addition, to determine the adequate concentration of the ethanolic extract ointment of the leaves of Dodonaea viscosa Jacq. "Chamisa" and to detect if the secondary metabolites participate jointly in the cicatrizing effect. Materials and Methods: An experimental study was carried out at the application level, with seven groups in total and a sample of 56 Balb/c-53 mice. The method tensiometric and Vaisberg were applied, analysis of the healing test was performed using data collection instruments and finally, the statistical program SPSS 24 was used. Results: The variability of the differences between the control groups and the three Chamisa concentration treatments was observed. Conclusion: it was determined that the ointment of the ethanolic extract of Dodonaea viscosa Jacq. "Chamisa" at 10% shows cicatrizant activity at 75.42%. It was found that the ointment of Dodonaea viscosa Jacq. "Chamisa" 10%, has a higher percentage of healing compared to the positive control, Croton lechleri ointment "Sangre de Drago" 10% (54.91% of the healing test). The phytochemical gait detected in the ethanolic extract of the leaves of Dodonaea viscosa Jacq. "Chamisa" contains: Phenolic Compounds, Flavonoids, Alkaloids and Tannins.